NILAI KARAKTER CERITA ANAK SEBAGAI MEDIA PENGUATAN PENDIDIKAN KARAKTER - Gafur, Abd; Lutfi, Moh; Sapta, Andy; Jameel, Ami Hibatul (Universitas Islam Sumatera Utara, 2023)
Literature as a function of entertainment and guidance will not be separated from the so-called value. This then underlies the importance of learning literature in elementary schools to instill character education. Literature can be a bridge between teachers and students in schools in an effort to cultivate positive character values. One of the literary works that can be used as a medium for character education in schools is children's stories. This research is a qualitative descriptive research with the object of research in the form of children's story text. The use of a descriptive qualitative approach in this study aims to provide a real and clear picture of the results of an in-depth analysis of the research object. The results of the study show that children's stories can be a bridge or media in strengthening character education in elementary schools. A collection of children's stories entitled